Benzobisoxazole Cruciforms: A Cross‐conjugated Platform for Designing Tunable Donor/Acceptor Materials. Issue 1 (19th November 2020) - Burney‐Allen, Alfred A.; Shaw, Jessica; Wheeler, David L.; Diodati, Lily; Duzhko, Volodimyr; Tomlinson, Aimée L.; Jeffries‐EL, Malika
Abstract: Four cross‐conjugated molecules based on the benzo[1, 2‐ d :4, 5‐ d' ]bisoxazole (BBO) moiety have been synthesized from a common synthon. Theoretical studies indicated that these cruciforms had highly segregated HOMO and LUMO levels enabling semi‐autonomous tuning of the LUMO level from the HOMO through substitution along the 2, 6‐axis. The experimental data confirms that the HOMO levels within these systems varied by 0.3 eV, whereas the LUMO levels varied by over 1.6 eV when the electron‐density along the 2, 6‐axis was increased. The introduction of relatively electron‐deficient moieties along the 2, 6‐axis resulted in a bathochromic shift in the absorption profiles concurrent with the stabilization of the LUMO. These substituents also prolonged the photoluminescent lifetimes owing to improved intramolecular charge transfer states between the 4, 8‐ and 2, 6‐ axis. The BBO cruciforms were evaluated as donor materials in organic solar cells (OSC)s, but the energy‐level mismatches and poor thin film morphology led to poor performance. These results indicate that benzobisoxazole cruciforms are a promising platform for the development of tunable materials for use in organic semiconductors, but improvements in the optical, electronic and film‐forming properties are needed to enable their use in efficient OSCs. Abstract : A series of cross‐conjugated organic semicoductors were synthesized and investigated for use as a tunable platform for the development of materials for use in organic solar cells.